DESIGN OF PLASTISOL INK DRYER FOR T-SHIRT SCREEN PRINTING WITH FLASH CURING - Dharmawan, Achmad Boby Adi; Saputra, Dwi Hadidjaja Rasjid (Journal for Technology and Science, 2025)
Objective: T-shirt screen printing ink drying can be done with various methods and tools such as fans, hair dryers, or heatguns. Although common and easy to do, these methods of drying t-shirt screen printing ink are less effective and efficient because they take a long time and the drying results are uneven. This research aims to make an effective and efficient plastisol screen printing ink dryer with flash curing using the research and development method. Method: This research aims to make an effective and efficient plastisol screen printing ink dryer with flash curing using the research and development method. Results: The results showed that the drying process with the tool made took 20 seconds for each shirt, 5 seconds faster than the ink drying test with the manual method. The tool made uses a synchronous motor to move the infrared heater forward and backward so that the ink drying results can be evenly distributed. Novelty: This research aims to make an effective and efficient plastisol screen printing ink dryer with flash curing using the research and development method.